2022
DOI: 10.3390/biomedicines10081842
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies to Enhance Tumor Antigenicity: Making the Tumor Detectable by the Immune System

Abstract: Cancer immunotherapy has revolutionized the oncology field, but many patients still do not respond to current immunotherapy approaches. One of the main challenges in broadening the range of responses to this type of treatment is the limited source of tumor neoantigens. T cells constitute a main line of defense against cancer, and the decisive step to trigger their activation is mediated by antigen recognition. Antigens allow the immune system to differentiate between self and foreign, which constitutes a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…For example, epigenetic drugs or splicing modulatory drugs can induce the expression of cryptic universal antigens such as testis antigens 12 or aberrant splicing variants. 13 Another strategy may involve blocking the nonsense-mediated mRNA decay (NMD) 14,51 . NMD is an RNA surveillance process that eliminates mRNA containing premature stop codons (PTC) that mainly appear during transcription by RNA polymerase errors or during RNA maturation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, epigenetic drugs or splicing modulatory drugs can induce the expression of cryptic universal antigens such as testis antigens 12 or aberrant splicing variants. 13 Another strategy may involve blocking the nonsense-mediated mRNA decay (NMD) 14,51 . NMD is an RNA surveillance process that eliminates mRNA containing premature stop codons (PTC) that mainly appear during transcription by RNA polymerase errors or during RNA maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Antigens enable the immune system to distinguish body's own tissues and cancer cells. Neoantigens are derived from about 10% of the non-synonymous somatic mutations and play an important role in antitumor response [32], for they are main targets of T-cellmediated antitumor immunity [33]. In this study, EPHA3-Mut group showed higher TMB and NAL level, indicating that EPHA3 mutation may be associated with better prognosis of NSCLC patients receiving immunotherapy.…”
Section: Dicussionmentioning
confidence: 56%
“…In therapeutic contexts, strategies to enhance antigen presentation and MHC expression have shown promise in boosting CYT and overcoming immune evasion by tumors. For example, treatments that increase the visibility of tumor antigens to the immune system, thereby facilitating their recognition and destruction by CTLs, directly contribute to elevating CYT levels within the tumor microenvironment (TME) [64]. This approach not only underscores the therapeutic potential of targeting antigen presentation pathways, but also highlights the crucial role of the MHC in modulating immune responses against cancer.…”
Section: • Antigen Presentation and Mhc Expressionmentioning
confidence: 99%